2013
DOI: 10.1007/s11748-013-0255-z
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis regarding patch size, stiffness, and contact condition to the endocardium in surgery for post infarction ventricular septal rupture

Abstract: In endocardial patch type surgery for VSR, proper sizing of the patch to sufficiently fit to endocardial surface in a tension-free condition is the most important to avoid residual leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The patch was a composite one in which the blood contact surface was the bovine pericardium and septal sur-face was Dacron, Teflon, and ePTFE attached together by GRF glue or fibrin glue. We observed a major leak when the size discrepancy of the patch and trimmed VSD was < 30 mm 14) ; it was confirmed by mathematical analysis that a smaller size tended to cause the leak by Ito et al 22) .…”
Section: Major Leak and Patch Sizesupporting
confidence: 80%
See 1 more Smart Citation
“…The patch was a composite one in which the blood contact surface was the bovine pericardium and septal sur-face was Dacron, Teflon, and ePTFE attached together by GRF glue or fibrin glue. We observed a major leak when the size discrepancy of the patch and trimmed VSD was < 30 mm 14) ; it was confirmed by mathematical analysis that a smaller size tended to cause the leak by Ito et al 22) .…”
Section: Major Leak and Patch Sizesupporting
confidence: 80%
“…3b and 5d). Although we attempted plication of the leak Midterm survival data from our study (13) and other studies (19)(20)(21)(22) are shown.…”
Section: Surgical Correction Of Major Leakmentioning
confidence: 72%
“…[1][2][3][4][5][6] The technique involves either a left ventricular (LV) or right ventricular (RV) incision approach. Hospital mortality has been reported as 17.6%-36.4% for an LV approach, [1][2][3] and 14.3%-20% for an RV approach. 4,6 Recently, an extended sandwich patch technique through an RV incision has been proposed and attracted surgeons' interest.…”
Section: Introductionmentioning
confidence: 99%
“…Their 13.6% of in-hospital mortality was striking, therefore, many surgeons adopted this technique and several modifications of this technique were proposed. In the discussion record of meeting presentation of this paper, Daggett mentioned that "I am unable to decide whether the results that Dr. David has been able to We [4] previously reported geometrical property of patch closure of post infarction VSR using finite element analysis. A large patch that closely contact to endocardium of the left ventricle decreased the stress on the suture line.…”
mentioning
confidence: 96%
“…Surgical glue may be an answer. Also in left ventricular approach, by gluing felt strips to the epicardium, bleeding from the closure line of the ventricle can be prevented [4]. If sandwich technique is performed as a mirror image through left ventricular approach as Caimmi et al reported [5], placing larger patch on the left ventricular side becomes easier compared with original right ventricular approach.…”
mentioning
confidence: 99%